The Role of Recycling in Building a Circular Economy (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2026)
The growing global demand for resources and increasing waste generation pose serious threats to sustainable development (UNEP, 2023). Transitioning from a linear to a circular economy has become crucial. This article analyzes the environmental, social, and economic benefits of recycling, illustrated by practices in Sweden and the European Union. Findings indicate that recycling contributes to energy savings, waste reduction, job creation, and economic resilience. Nevertheless, recycling alone is insufficient without systemic approaches and supportive policies (Circularity Gap Report, 2024).